Pedagogic Competence as A Key Factor in the Successful Implementation of the Islamic Religiuous Education Curriculum - Suni Amanah (Global Journal of Islamic Education, 2025)
This study aims to explore the implementation of the Islamic Religious Education (IRE) Curriculum  and the influence of teachers' pedagogic competence on learning and student character formation. Good pedagogic competence of teachers is believed to improve the quality of PAI teaching, which is not only focused on the cognitive aspect but also on the character aspect of students. This study uses a qualitative approach with a type of case study that involves direct observation, in-depth interviews with teachers and students, and documentation related to the implementation of the curriculum in several schools. The results of the study show that although the IRE curriculum is well structured and in accordance with the needs, several significant challenges are found, such as limited educational facilities, lack of technology-based training, and a lack of in-depth understanding of pedagogic competence among most teachers. Therefore, to increase the effectiveness of learning, strategies are needed to improve teachers' pedagogic competence, including through continuous training and the provision of more adequate educational facilities. The optimal implementation of the IRE curriculum is expected to create a more meaningful learning environment, so that it can form the character of students who are not only intellectually intelligent, but also have noble character in daily life.